2020
DOI: 10.1109/tvt.2020.3041843
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated Polar Feature-Based Deep Learning for Efficient and Lightweight Automatic Modulation Classification With Channel Compensation Mechanism

Abstract: In next-generation communications, massive machine-type communications (mMTC) induce severe burden on base stations. To address such an issue, automatic modulation classification (AMC) can help to reduce signaling overhead by blindly recognizing the modulation types without handshaking. Thus, it plays an important role in future intelligent modems. The emerging deep learning (DL) technique stores intelligence in the network, resulting in superior performance over traditional approaches. However, conventional D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Teng et al [5] extend their previous work in [91] and proposed an accumulated polar feature-based DL with a channel compensation mechanism. In [91], they have shown that learning features from polar coordinates, which can be obtained from Cartesian coordinates, can achieve higher recognition accuracy.…”
Section: D: Classification Using Other Inputsmentioning
confidence: 82%
See 1 more Smart Citation
“…Teng et al [5] extend their previous work in [91] and proposed an accumulated polar feature-based DL with a channel compensation mechanism. In [91], they have shown that learning features from polar coordinates, which can be obtained from Cartesian coordinates, can achieve higher recognition accuracy.…”
Section: D: Classification Using Other Inputsmentioning
confidence: 82%
“…In [91], they have shown that learning features from polar coordinates, which can be obtained from Cartesian coordinates, can achieve higher recognition accuracy. Then in [5], they add a new temporal axis to accumulate historical information of symbols in such dimension. In the proposed method, the polar coordinates were projected to grid-like images.…”
Section: D: Classification Using Other Inputsmentioning
confidence: 99%
“…In this paper, the I/Q format of the original complex sample is mainly converted to A/P format; in other words, the original sample is converted from I/Q coordinates to polar coordinates [7]. In literature [15], the author directly mapped the received complex symbols to the constellation map on the complex plane as features and achieved good performance.…”
Section: Signal Preprocessingmentioning
confidence: 99%
“…To cope with a more complex realistic environment and reduce the influence of channels on transmitted signals, an improved CNN method is proposed in [6] to correct signal distortion that may occur in wireless channels. In [7], a channel estimator based on neural network is designed to find the inverse channel response and improve the accuracy of the network by reducing the influence of channel fading [8]. Based on the theoretical knowledge of signal parameter estimation, a parameter estimator is introduced to extract information related to phase offset and transform phase parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [21] proposed a robust modulation classifier in an uncertain noise channel environment by adopting the attention mechanism to the output of an LSTM layer. To compensate for the fading channel characteristics, Teng et al [32] proposed a CNN technique to estimate the channel response for improving modulation classification using the accumulated amplitude and phase data.…”
Section: Related Workmentioning
confidence: 99%